Protection Of Social Media Users' Personal Data From An International Law Perspective and Its Application In Indonesia - Rezti Aisyahbella; Adya Paramita Prabandari (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid development of digital technology has enabled widespread communication through social media, yet it has simultaneously exposed millions of users to serious risks of personal data leakage and misuse. Objective: This study aims to analyze personal data protection for social media users from an international law perspective and examine its application within the Indonesian legal framework. Methods: This research employs a normative juridical approach using statutory, conceptual, and comparative methods, analyzing primary, secondary, and tertiary legal materials through descriptive-qualitative techniques. Results: International personal data protection law is governed by a range of international legal frameworks, including the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). Both the UDHR and ICCPR apply globally and emphasize that the right to privacy is a fundamental aspect of human rights. Indonesia ratified the ICCPR through Law No. 12 of 2005, which pertains to the ratification of the International Covenant on Civil and Political Rights. Furthermore, the safeguarding of personal data is addressed in Law Number 11 of 2008 on Information and Electronic Transactions, and further detailed in Law Number 27 of 2022, which focuses on the Protection of Personal Data. However, challenges in implementation remain, particularly regarding the classification of children's data and the establishment of an independent supervisory authority for personal data protection. Conclusion: Strengthening legal implementation, ensuring social media platform compliance, and developing derivative regulations are essential to effectively protect social media users’ personal data in Indonesia.